Long‐term safety of certolizumab pegol in plaque psoriasis: pooled analysis over 3 years from three phase III, randomized, placebo‐controlled studies. (6th September 2020) - Blauvelt, A.; Paul, C.; van de Kerkhof, P.; Warren, R.B.; Gottlieb, A.B.; Langley, R.G.; Brock, F.; Arendt, C.; Boehnlein, M.; Lebwohl, M.; Reich, K.
Summary: Background: Certolizumab pegol (CZP) is an Fc‐free, PEGylated anti‐tumour necrosis factor biologic. Objectives: To report 3‐year safety data from three phase III trials of CZP in adults with plaque psoriasis. Methods: Data were pooled from CIMPASI‐1 (NCT02326298), CIMPASI‐2 (NCT02326272) and CIMPACT (NCT02346240). Included patients had moderate‐to‐severe plaque psoriasis of ≥ 6 months' duration; had been randomized to CZP 200 mg every 2 weeks (Q2W) (400 mg at weeks 0, 2 and 4) or CZP 400 mg Q2W; and had received at least one dose of CZP with up to 144 weeks of exposure. Treatment‐emergent adverse events (TEAEs) were classified using MedDRA v18·1. Reported incidence rates (IRs) are incidence of new cases per 100 patient‐years (PY). Results: Over 144 weeks, 995 patients received at least one dose of CZP (exposure: 2231·3 PY); 731 and 728 received at least one dose of CZP 200 mg Q2W (1211·4 PY) and/or 400 mg Q2W (1019·9 PY), respectively. The IR [95% confidence interval (CI)] of TEAEs was 144·9 (135·3–155·0) for all patients, 134·1 (123·2–145·7) for CZP 200 mg Q2W and 158·3 (145·5–171·9) for CZP 400 mg Q2W. The IR (95% CI) of serious TEAEs for all patients was 7·5 (6·4–8·8); the IRs were 6·7 (5·2–8·3) and 8·7 (6·9–10·8) for CZP 200 mg and 400 mg Q2W, respectively. Overall, 3·2% of patients reported serious infections (2·2% within each of the CZP 200 and 400 mg Q2W groups). Overall, there was one case of active tuberculosis, 16 malignancies in 14 patients and seven deaths (two considered treatment‐related). The cumulative IR of TEAEs did not increase over time. Conclusions: No new safety signals were identified compared with previously reported data. Risk did not increase with longer or higher CZP exposure. Abstract : What is already known about this topic? Certolizumab pegol is an Fc‐free, PEGylated, anti‐tumour necrosis factor biologic approved for adults with moderate‐to‐severe plaque psoriasis. Safety data from phase III trials in plaque psoriasis have found the incidence of adverse events to be generally similar over 16 weeks of treatment between the evaluated certolizumab pegol doses 200 mg and 400 mg every 2 weeks and placebo. Additionally, the safety profile was in line with the class over 48 weeks. What does this study add? Plaque psoriasis is a chronic disease for which patients require lifetime management; long‐term safety data are important to understand the benefits and risks of prolonged treatment. Here, 3‐year data from a pooled analysis of three phase III trials of certolizumab pegol in plaque psoriasis are presented, representing 2231·3 patient‐years of exposure. No new safety signals were identified and the risk of treatment‐emergent adverse events did not increase with longer or higher certolizumab pegol exposure.